Obesity as a risk factor of hypertension - Istomina, Olga; Kisilenko, Katerina (My University, 2014)
Istomina Olga, Kisilenko Katerina Obesity as a risk factor of hypertension Department of Fundamentals of Internal Medicine N1, Fundamentals of Bioethics and BiosafetyScientific Director: MD, professor O.N. Kovalyova Kharkiv National Medical University Kharkiv, Ukraine Obesity at the present time is the most known and recognized metabolic disease, become as common, as an epidemyc in developed countries, and in developing countries too. Average index by obesity in Ukraine in 2012 year is 1231 person per 100 thousand population. Obesity, is a risk factor for a lot of diseases, especially for arterial hypertension (AH).Characteristic changes in this combination will be: left ventricular hypertrophy (probability of occurrence of it in individuals with normal body weight is 5,5% and with obesity-29,9%), increased heart weight, myocardial remodeling of left ventricular and it's diastolic dysfunction, and in a result leads to reduced quality of life.It's known, that hypertension meets twice more in individuals with overweight, that why antihypertensive medication must be more aggressive and need more dosage of it.In the world-famous research Framingham Heart Study was noted that the risk of new cases of hypertension was highly associated with overweight, in comparison with people with normal body weight (BMI = 18,5 – 24,9) and it's for woman-1,75, for men-1,46. Also they notice, that obesity shortens lifespan by 6-7 years. In Tanno-Sobetus Study was determined that risk of development of AH increased by abdominal obesity type in 2,33 times. But, it should be remembered that obesity is modifiable.In accordance with Guidelines for the management of AH 2013 ESH/ESC doctor should focus on reducing body weight by 5 -15% over 6 months:patient should eat more vegetables,fruits; regular exercise; downgrading of body weight to a BMI of 25 kg/m2 and waist circumference to <102 cm for men and <88 cm for women and maintain blood pressure of <140/90 mmHg.
Istomina Olga, Kisilenko Katerina Obesity as a risk factor of hypertension Department of Fundamentals of Internal Medicine N1, Fundamentals of Bioethics and BiosafetyScientific Director: MD, professor O.N. Kovalyova Kharkiv National Medical University Kharkiv, Ukraine Obesity at the present time is the most known and recognized metabolic disease, become as common, as an epidemyc in developed countries, and in developing countries too. Average index by obesity in Ukraine in 2012 year is 1231 person per 100 thousand population. Obesity, is a risk factor for a lot of diseases, especially for arterial hypertension (AH).Characteristic changes in this combination will be: left ventricular hypertrophy (probability of occurrence of it in individuals with normal body weight is 5,5% and with obesity-29,9%), increased heart weight, myocardial remodeling of left ventricular and it's diastolic dysfunction, and in a result leads to reduced quality of life.It's known, that hypertension meets twice more in individuals with overweight, that why antihypertensive medication must be more aggressive and need more dosage of it.In the world-famous research Framingham Heart Study was noted that the risk of new cases of hypertension was highly associated with overweight, in comparison with people with normal body weight (BMI = 18,5 – 24,9) and it's for woman-1,75, for men-1,46. Also they notice, that obesity shortens lifespan by 6-7 years. In Tanno-Sobetus Study was determined that risk of development of AH increased by abdominal obesity type in 2,33 times. But, it should be remembered that obesity is modifiable.In accordance with Guidelines for the management of AH 2013 ESH/ESC doctor should focus on reducing body weight by 5 -15% over 6 months:patient should eat more vegetables,fruits; regular exercise; downgrading of body weight to a BMI of 25 kg/m2 and waist circumference to <102 cm for men and <88 cm for women and maintain blood pressure of <140/90 mmHg.
Keywords: hypertension; obesity